L-Fuzzy Connectedness in Stratified Order-Preserving Operator Spaces - Xiu-Yun Wu; Li-Li Xie; Liang-Sheng Huang (Advances in Fuzzy Systems)
The concepts of stratified order-preserving operators and stratified continuity are introduced in L-fuzzy topological spaces. Their basic properties are discussed, and their characteristic properties are observed. The relationship between induced stratified order-preserving topological spaces and general order-preserving operator topological spaces is studied. Finally, stratified connectedness is introduced, and its properties are studied systematically.